Comparing Professional Self-Confidence: Opinions of Lithuanian, Ukrainian and Finnish Teachers - Tetiana Ponomarenko (European Scientific Journal, ESJ, 2017)
The current study reports findings of quantitative investigation of the opinions of Lithuanian, Ukrainian and Finnish teachers on their perceived professional self-confidence with a sample of 393 practicing teachers. Teachers’ self-esteem, self- and collective efficacy were examined as components of teachers’ professional self-confidence. Collective efficacy beliefs were measured in terms of teachers’ subjective perception of efficacy of school community members, namely, the principal, colleagues, students and their parents. The results indicated that Finnish teachers have a significantly higher level of professional self-esteem, while Lithuanian teachers indicated a lower level, and Ukrainian - the lowest. There is no significant difference between self- and collective efficacy of Lithuanian and Finnish teachers, while Ukrainian teachers scored significantly lower. Consequently, Finnish teachers have the highest level of professional selfconfidence, while Lithuanian teachers have an average level, and Ukrainian teachers have the lowest. Lithuanian, Ukrainian and Finnish teachers indicated different patterns of their perceptions of the extent to which members of the school community meet their obligations.